2010
DOI: 10.1118/1.3475940
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between diffusion‐weighted imaging, ‐weighted, and postcontrast ‐weighted imaging after MR‐guided, high intensity, focused ultrasound treatment of uterine leiomyomata: Preliminary results

Abstract: Purpose:To investigate the comparison between diffusion-weighted imaging ͑DWI͒, T 2 -weighted imaging, ͑T 2 WI͒ and contrast T 1 -weighted imaging ͑cT 1 WI͒ in uterine leiomyoma following treatment by magnetic resonance imaging-guided, high intensity focused ultrasound surgery ͑MRg-HIFUS͒. Methods: Twenty one patients ͑45Ϯ 5 yrs͒ with clinical symptoms of uterine leiomyoma ͑fibroids͒ were treated by MRg-HIFUS using an integrated 1.5T MRI-HIFUS system. MRI parameters consisted of DWI, T 2 WI, and T 1 -weighted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 56 publications
(73 reference statements)
1
11
0
Order By: Relevance
“…Similar to the ex vivo study a significant ADC increase was observed instantly after HIFU treatment of subcutaneous mouse tumors and muscle tissue . In contrast, a significant decrease in ADC was found directly after treatment of uterine fibroids (Fig. A).…”
Section: Mri‐detectable Hifu Treatment Effectssupporting
confidence: 82%
See 1 more Smart Citation
“…Similar to the ex vivo study a significant ADC increase was observed instantly after HIFU treatment of subcutaneous mouse tumors and muscle tissue . In contrast, a significant decrease in ADC was found directly after treatment of uterine fibroids (Fig. A).…”
Section: Mri‐detectable Hifu Treatment Effectssupporting
confidence: 82%
“…Jacobs et al used a multiparametric analysis using diffusion‐weighted and contrast‐enhanced T 1 ‐weighted images to segment successfully treated and nontreated tissue directly after HIFU treatment of uterine fibroids. Excellent agreement was observed between the segmentations based on both MRI methods . We have recently performed cluster analysis on multiparametric MRI data obtained after HIFU treatment of subcutaneous mouse tumors.…”
Section: Mri‐detectable Hifu Treatment Effectsmentioning
confidence: 78%
“…Tissue response might become more apparent some hours after treatment [29]. Next to T2W MR imaging, other MR imaging techniques such as (dynamic) contrast-enhanced MR imaging, diffusion weighted, or T2* weighted MR imaging could be used for treatment evaluation and follow-up [21,[30][31][32][33]. It has previously been shown that the permeability of vessels increases, or the vessels are destroyed by mechanical destruction for example due to cavitation effects [8].…”
Section: Discussionmentioning
confidence: 97%
“…Native T 1 ‐weighted images also have a zonal appearance that matches histology but has lower contrast . Diffusion‐weighted imaging (DWI) and apparent diffusion coefficient (ADC) mapping depict a mix of increased ADC due to disruption of cell membranes, and decreased ADC due to cell swelling and vascular shutdown . Intravoxel incoherent motion (IVIM) estimates tissue perfusion in addition to diffusion, and may improve specificity .…”
Section: Discussionmentioning
confidence: 99%